2014
DOI: 10.1039/c4cp02322f
|View full text |Cite
|
Sign up to set email alerts
|

Use of side-chain for rational design of n-type diketopyrrolopyrrole-based conjugated polymers: what did we find out?

Abstract: The primary role of substituted side chains in organic semiconductors is to increase their solubility in common organic solvents. In the recent past, many literature reports have suggested that the side chains play a critical role in molecular packing and strongly impact the charge transport properties of conjugated polymers. In this work, we have investigated the influence of side-chains on the charge transport behavior of a novel class of diketopyrrolopyrrole (DPP) based alternating copolymers. To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 34 publications
1
69
2
Order By: Relevance
“…Compared to the band gaps of DPP polymers without a vinylene linkage (e.g., 2DPP-OD-OD, ΔE g = 1.22 eV), which were previously reported by our group, 48 the optical band gap increases due to inclusion of the vinylene unit in the polymer backbone. 48 2.3. Theoretical Calculations.…”
Section: Scheme 1 Synthesis Of Three Vinylene Dpp Based Copolymersmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared to the band gaps of DPP polymers without a vinylene linkage (e.g., 2DPP-OD-OD, ΔE g = 1.22 eV), which were previously reported by our group, 48 the optical band gap increases due to inclusion of the vinylene unit in the polymer backbone. 48 2.3. Theoretical Calculations.…”
Section: Scheme 1 Synthesis Of Three Vinylene Dpp Based Copolymersmentioning
confidence: 85%
“…48 Hence, close proximity of a very long and branched alkyl chain appears to be detrimental for molecular packing and consequently for measurable charge transport in the device channel. Here the vinylene group acts as a spacer between two DPP units to reduce the interchain repulsive interaction.…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
“…[29][30][31] As a newly-developed derivative of DPP, SMDPPEH hosts two pendant alkyl chains, which increases its solubility and thermal stability. 32 The molecular structure of SMDPPEH is shown in Figure 1(a).…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37][38] Several research groups have reported electron mobility values surpassing 1 cm 2 V -1 s -1 for FETs based on DPPcontaining polymers. [39][40][41][42] In comparison, the development of n-type DPP-based small molecules, which possess advantages over polymers including ease of purification and less variation between batches, has been largely lagged behind. 43 In our search for high-performance n-type OSCs, we focused on DPP-containing quinoidal small molecules with dicyanovinyl terminal groups.…”
Section: Introductionmentioning
confidence: 98%